Cranium-Penetrating Mass Detected by Ultrasound Expedited Management of Langerhans Cell Histiocytosis. Issue 4 (April 2017) - Morgan, Brian; Lau, Hsien Lee; Yellin, Sharon
Abstract : Abstract: A 6-year-old boy presented to the pediatric emergency department with a unilateral 5 × 3-cm superficial mass on the postauricular region growing for 1 month. Point-of-care ultrasound was used to evaluate the mass, which revealed a complex cystic mass penetrating the temporal bone. After confirmatory magnetic resonance imaging, the patient was transferred for neurosurgical evaluation, and the tumor was excised. Pathology revealed Langerhans cell histiocytosis.